2012
DOI: 10.1007/s11357-011-9359-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on the physical and cellular properties of the human limbal stem cell niche

Abstract: The limbal niche in the corneoscleral junction of the eye, habitat of the limbal epithelial stem cells (LESC), facilitates corneal epithelial regeneration by providing physical support and chemical signalling. Anatomical structures within the limbus, namely, limbal epithelial crypts and focal stromal projections, are believed to function as a putative niche for LESCs. In this study, the impact of age on the topography of this niche was investigated. Also, the relationship between niche topography and limbal ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 44 publications
7
50
1
4
Order By: Relevance
“…However, the levels of putative stem cell markers and telomere length or telomerase activity do not show differences between ages [42]. Our results fit with these findings, as LSC from donors older than 60 years showed higher levels of the putative stem cell marker p63.…”
Section: Discussionsupporting
confidence: 89%
“…However, the levels of putative stem cell markers and telomere length or telomerase activity do not show differences between ages [42]. Our results fit with these findings, as LSC from donors older than 60 years showed higher levels of the putative stem cell marker p63.…”
Section: Discussionsupporting
confidence: 89%
“…The influence of age on the niche topography has previously been described by Notara et al 20 Although the age range of the study population was narrow, we revealed an influence of age on the parameters for the right inferior (PD and Δ ERP ) and left superior (PD, Δ PR and Δ ERP ) limbal region. No influence was found for subject gender, although gender was not distributed equally.…”
Section: Discussionsupporting
confidence: 74%
“…After isolating epithelial cells for culture, as described previously, 18,19 the scleral and corneal part of the rims were cut off to leave approximately 1 mm on either side of the limbus. Subsequently, the tissue was dissected further into smaller fragments.…”
Section: Isolation and Culture Of Human Limbal Fibroblastsmentioning
confidence: 99%
“…As previously mentioned, it furthermore has been linked to effects of UV radiation. 18 While the main concern of most studies has been the assessment of the impact of UVB in the occurrence of pterygium, cataract, and skin tumors, the impact of UVA so far has been poorly studied. Epidemiologic studies have shown that the occurrence of pterygium was associated significantly with UVA and UVB.…”
mentioning
confidence: 99%